1998
DOI: 10.1126/science.279.5358.1943
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Intermediates Trapped by Native Interactions in RNA Folding

Abstract: In the magnesium ion-dependent folding of the Tetrahymena ribozyme, a kinetic intermediate accumulates in which the P4-P6 domain is formed, but the P3-P7 domain is not. The kinetic barriers to P3-P7 formation were investigated with the use of in vitro selection to identify mutant RNA molecules in which the folding rate of the P3-P7 domain was increased. The critical mutations disrupt native tertiary interactions within the P4-P6 domain and increase the rate of P3-P7 formation by destabilizing a kinetically tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
177
0
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(188 citation statements)
references
References 29 publications
7
177
0
2
Order By: Relevance
“…Folding is represented as a single step, representing attainment of catalytic competence. In reality, folding is probably several distinct steps, as has been seen for other RNAs (40)(41)(42)(43). Furthermore, Scheme 1 begins with substrate bound to the ribozyme prior to folding and disregards the contribution of Mg 2+ -dependent folding prior to substrate association.…”
Section: Role Of Metal Ions In Structure Andmentioning
confidence: 99%
“…Folding is represented as a single step, representing attainment of catalytic competence. In reality, folding is probably several distinct steps, as has been seen for other RNAs (40)(41)(42)(43). Furthermore, Scheme 1 begins with substrate bound to the ribozyme prior to folding and disregards the contribution of Mg 2+ -dependent folding prior to substrate association.…”
Section: Role Of Metal Ions In Structure Andmentioning
confidence: 99%
“…Paradoxically, some RNA structural elements seem to exacerbate misfolding; studies of the group I intron from Tetrahymena have shown that its P5abc domain stabilizes misfolded intermediates and dramatically slows refolding of these intermediates into the native state [11,29,30]. P5abc's detrimental effect on folding kinetics is balanced by its ability to confer thermodynamic stability to the native state and enhance its catalytic activity [31,32].…”
Section: How Atp-dependent Rna Chaperones Assist Foldingmentioning
confidence: 99%
“…where ⌬G I ‡ is the free energy difference between I and the transition state (Fig+ 2)+ Metastable folding intermediates in RNA are stabilized by many native (as well as some non-native) interactions (Pan & Woodson, 1998;Treiber et al+, 1998)+ Because the transition state is expected to share some features with I and N, changes in ⌬G I ‡ (due to mutations, for example) may be predicted from changes in the relative free energies of I and N (or U and N for mechanisms not involving I), as demonstrated for the Tetrahymena pre-rRNA )+ Hence, the transition state energy is proportional to ⌬G UN , and ⌬G I ‡ can be estimated from ⌬G I ‡ ' Ϫ⌬G UN + This conclusion is reached by considering that the folded structures of biological macromolecules are stabilized by many noncovalent interactions, which are on the order of a few k B T (0+5-2 kcal/mol)+ Because this energy is comparable to the entropy lost when an ordered structure is formed, the folded state is only marginally stable (for the Mg 2ϩ -dependent transition of the Tetrahymena pre-rRNA, ⌬G UN ' 4+5 kcal/mol ϭ 7+5 k B T)+ Typical free energy barriers in RNA folding result from the same types of noncovalent interactions+ Hence, these barriers are also minimized by compensating enthalpy and entropy changes+ Because many of the interactions that stabilize I are native contacts, the free energy penalty for partially unfolding I must scale with the stability of N+ Assuming that ⌬G interface and ⌬S interdomain do not depend on the stabilities of the individual domains and contribute less to the stability of I, then the transition state energy ⌬G I ‡ ' Ϫ(⌬G 46 ϩ ⌬G 39 )+ It follows from equation (2) …”
Section: Transition States and The Stability Of Domainsmentioning
confidence: 99%
“…1+ Because the P4-P6 domain is more stable than P3-P9 in the wild-type ribozyme, the folding pathway is characterized by intermediates in which tertiary interactions within P4-P6 are formed (Celander & Cech, 1991;Zarrinkar & Williamson, 1994;Sclavi et al+, 1998) but P3 and P7 are misfolded (Pan & Woodson, 1998;Pan et al+, 2000)+ Let us assume that formation of the native interface between the two domains requires some loosening of interactions within each domain+ Because P3 and P7 appear to be disordered and to contain few stable tertiary contacts in the I states, the P3-P9 domain is expected to be more flexible than the P4-P6 domain+ Hence, the minimum barrier for the I-to-N transition is expected to be dominated by ⌬G 46 , so that equation (3) reduces to t Ն exp(a⌬G 46 ), where a is a scaling factor that is proportional to Ϫ1/RT+ This estimate for t neglects contributions from non-native interactions to the stability of I, which moderately increase ⌬G I ‡ and t+ This situation corresponds to the left side of the curve in Figure 3, in which the folding time becomes progressively shorter as the stability of the P4-P6 domain is decreased+ In a search for fast-folding mutants, Treiber et al+ (1998) found that mutations that destabilized tertiary interactions within the P5abc region of the P4-P6 domain increased the folding rate of P3 and P7 up to fivefold at 37 8C+ Similarly, mutations that disrupt base pairing between the loops of P5c and P2 increase the overall folding rate of the ribozyme )+ 2+ ⌬G 46 /⌬G 39 , 1+ If interactions in the P3-P9 domain are more stable than those in the P4-P6 domain, then according to the reasoning above, we expect the free energy barrier for forming the native structure to be proportional to ⌬G 39 , and t ' exp(a⌬G 39 )+ This situation is illustrated by the right side of the curve in Figure 3+ A key prediction of this model is that it should be possible to reverse the order in which the domains fold by introducing mutations that significantly stabilize P3-P9 relative to the P4-P6 domain+ 3+ ⌬G 46 /⌬G 39 ' 1+ Figure 3 shows that the trends above converge when the stabilities of the two domains are roughly equal+ Generally, we expect that the folding time, t ' exp(2a⌬G 39 ) will approach a minimum when ⌬G 46 ' ⌬G 39 + We have recently found that a mutation in the P3 helix of the Tetrahymena ribozyme increases the stability of the P3-P9 domain so that it folds at similar Mg 2ϩ concentrations as the P4-P6 domain (Pan et al+, 2000)+ As predicted by this model, the overall folding rate is increased 10-to 50-fold by this mutation, and the majority of the RNA (;80%) reaches the native state without becoming trapped in metastable intermediates (Fig+ 2)+ Although the examples above ignore contributions to the transition state energy from interactions at the domain interface, a similar analysis is obtained if the ratio ⌬G 46 /⌬G 39 is compared to (1 ϩ b/⌬G 39 ), where b ϭ ⌬G interface Ϫ T⌬S interdomain + If b . ⌬G 39 , then the overall folding rate will be dominated by interdomain interactions and will be less sensitive to the energetics for folding the independent domains+ We also acknowledge that the RNA folding problem has been simplified in this analysis, and other factors are likely to influence folding rates+ Nonetheless, this model qualitative...…”
Section: Maximizing Folding Rates By Modulating Domain Stabilitymentioning
confidence: 99%